Keanekaragaman Burung di Kawasan Babakan Siliwangi City Forest Path, Kota Bandung: Bird Diversity in Babakan Siliwangi City Forest Path, Bandung City - Shelvie Raffiza Nasihin; Eneng Nunuz Rohmatullayaly (Jurnal Sumberdaya Hayati, 2023)
Indonesia is a habitat for around 17% of the world’s bird species. Birds have an essential role, such as helping in pollination and seed dispersal, controlling insects, and as indicators of environmental change, hence their existence needs to be maintained to maintain the balance of the ecosystem. Babakan Siliwangi City Forest Path Bandung is an urban and green open area used as a public area allowing it to be a habitat for various birds. Therefore, this study aimed to determine the diversity and birds at that location. The method used in this study is the point count method with ten observation points and five repetitions with one observation line. The results showed five species of birds with 45 individuals from four families, namely Passeridae, Apodidae, Pycnonotidae, and Dicruridae. The index value of bird species diversity in this area is moderate (1.20). The Cucak Kutilang (Pycnonotus aurigaster) had the highest abundance of bird species (58%), while the lowest was the Srigunting (Dicrurus macrocercus) (2%). In addition, the evenness of bird species is high (0.74) with no dominance (0.39) and low species richness (1.05). Thus, the Babakan Siliwangi City Forest Path Bandung area has ecosystem conditions to support a bird’s habitat.